Longitudinal thumbnail fissures due to erlotinib therapy for lung cancer. (April 2018) - Dasanu, Constantin A; Alvarez-Argote, Juliana; Lippman, Scott M; Plaxe, Steven C
While therapy with epidermal growth factor receptor inhibitors leads to meaningful clinical responses in several tumor types, it has also been linked with perplexing toxic effects. Skin effects of these agents such as generalized papulo-pustular rash, trichomegaly, fingertip fissures, xerosis, pruritus and paronichias are now well characterized. Though uncommon, nail atrophic changes have also been described in subjects treated with these classes of agents. We describe herein unusual longitudinal thumbnail fissures caused by erlotinib therapy for metastatic lung cancer. Unique features are bilateral thumbnail involvement and central location in the nail bed. This side effect of erlotinib has not been previously reported in the medical literature.